Evaluasi Bimbingan Bahasa Inggris Menggunakan Model Kirkpatrick - Sonia Eka Lestari; Fajri Dwiyama (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
In this day and age, English is also known as a much needed international language. People are increasingly required to be able to speak English both passively and actively. English language tutoring is one of the programs implemented at SMAN 13 Bone, which is evaluated using the Kirkpatrick model. The purpose of this study was to assess how the reaction, learning, application, and impact of English tutoring for students at SMAN 13 Bone. This study uses a qualitative approach with an exploratory case study method. This research was conducted at SMAN 13 Bone in the academic year 2022/2023. Data collection techniques used are interviews and observation. The results of the study showed that the implementation of English language guidance went well. This can be seen from the 4 stages, including: (1) Reactions caused by positive responses given by students regarding English language guidance, because the learning and the material are interesting. (2) Learn here about vocabulary, correct pronunciation, spelling, and even learning materials in class. (3) Its application involves the frequent application of English in daily life. (4) The impact of the English language guidance is an increase in students' understanding and report cards.